2021
DOI: 10.1002/aoc.6444
|View full text |Cite
|
Sign up to set email alerts
|

An overview of iron‐catalyzed N‐alkylation reactions

Abstract: N‐containing compounds are very important molecules in nature and in the field of synthetic organic chemistry. N‐alkylation reactions play crucial role in the area of pharmaceuticals and various other industrial chemical syntheses. Iron‐catalyzed N‐alkylation reactions have attained greater acceptance among the scientific community. Environmentally benign, abundant, nontoxic, biocompatible, reusable, and inexpensive iron catalysts are gaining more attention in various research fields. Green protocols, milder r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…N-substituted amines play an important role in the production of bulk and fine chemicals such as pharmaceuticals, polymers, agrochemicals etc. [2] Traditionally, this transformation has been carried out with stoichiometric amounts of toxic reagents such as alkyl halides that generates large amounts of waste. [3] However, in the last decade, using the BH methodology transition metal (TM) catalyzed Nalkylation reactions have been extensively explored generating only water as the byproduct (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…N-substituted amines play an important role in the production of bulk and fine chemicals such as pharmaceuticals, polymers, agrochemicals etc. [2] Traditionally, this transformation has been carried out with stoichiometric amounts of toxic reagents such as alkyl halides that generates large amounts of waste. [3] However, in the last decade, using the BH methodology transition metal (TM) catalyzed Nalkylation reactions have been extensively explored generating only water as the byproduct (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Various metal and ligand systems have been reported to operate via the BH methodology to carry out many important catalytic transformations [1a] one example being the N ‐alkylation of amines with alcohols. N ‐substituted amines play an important role in the production of bulk and fine chemicals such as pharmaceuticals, polymers, agrochemicals etc [2] . Traditionally, this transformation has been carried out with stoichiometric amounts of toxic reagents such as alkyl halides that generates large amounts of waste [3] .…”
Section: Introductionmentioning
confidence: 99%
“…4 Established pioneers of hydrogen shuttle catalysis have covered these methodologies to some extent in previous reviews focusing on relevant subtopics such as synthesizing heterocycles 5,6 and designing ligands. 7,8 Additionally, previous reviews have been published introducing the background and perspective of each individual metal separately: Co by Kundu 9 and Young, 10 Mn (Mukherjee), 11 Ru and Ir (Rit), 12 and Fe (Anilkumar), 13 to name but a few.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the microreactor technology has great potential in improving the selectivity and yield of N -monoalkylation of anilines. However, the hot topic in the N -monoalkylation reaction focuses on the development of a novel catalytic system for high selectivity . Few studies have reported the N -monoalkylation of anilines using the microreactor technology, especially for the process intensification through the use of a micromixer.…”
Section: Introductionmentioning
confidence: 99%
“…However, the hot topic in the Nmonoalkylation reaction focuses on the development of a novel catalytic system for high selectivity. 17 an interdigital micromixer was optimized based on numerical simulation. Meanwhile, the mixing performance of this micromixer was also evaluated through CFD simulation.…”
Section: Introductionmentioning
confidence: 99%